Analisis Pengukuran Kinerja Untuk Mengevaluasi Perencanaan Strategis Dengan Menggunakan Balance Scorecard - Wico Jontarudi Tarigan; Mahaitin H Sinaga (Politeknik Ganesha Medan, 2022)
Facing today's increasingly complex business environment, requires performance measurement that can accurately and thoroughly evaluate the performance of a company. In this case, the balanced scorecard method is used. In this case, the balanced scorecard method is used. The purpose of using the balanced scorecard method is to evaluate the strategic plan at PT. Jamsostek (Persero) Pematangsiantar Branch. The data analysis method used is descriptive qualitative and quantitative descriptive analysis to analyze the financial aspects of roi, liquidity ratios, profit margins, and operating ratios. From another perspective, are the results of customer acquisition, customer retention, company data on customer profitability, and interviews with customers and employees of PT. Jamsostek (Persero) Pematangsiantar Branch. Based on the results of the study, it was concluded that the effect was measured using the balanced scorecard of PT. Jamsostek (Persero) Pematangsiantar Branch overall is quite good. But from a financial point of view, for example, the level of ROI and profit margins has a more narrow view, which requires more attention when planning the next strategy for further improvement. The application of the balanced scorecard can be considered when evaluating strategic plans, because the balanced scorecard perspective can interpret the impact of changing trends on the company's vision, mission and goals in the future in a complex business environment